Adipocyte extracellular vesicles carry enzymes and fatty acids that stimulate mitochondrial metabolism and remodeling in tumor cells. (10th January 2020) - Clement, Emily; Lazar, Ikrame; Attané, Camille; Carrié, Lorry; Dauvillier, Stéphanie; Ducoux‐Petit, Manuelle; Esteve, David; Menneteau, Thomas; Moutahir, Mohamed; Le Gonidec, Sophie; Dalle, Stéphane; Valet, Philippe; et al.
Abstract: Extracellular vesicles are emerging key actors in adipocyte communication. Notably, small extracellular vesicles shed by adipocytes stimulate fatty acid oxidation and migration in melanoma cells and these effects are enhanced in obesity. However, the vesicular actors and cellular processes involved remain largely unknown. Here, we elucidate the mechanisms linking adipocyte extracellular vesicles to metabolic remodeling and cell migration. We show that adipocyte vesicles stimulate melanoma fatty acid oxidation by providing both enzymes and substrates. In obesity, the heightened effect of extracellular vesicles depends on increased transport of fatty acids, not fatty acid oxidation‐related enzymes. These fatty acids, stored within lipid droplets in cancer cells, drive fatty acid oxidation upon being released by lipophagy. This increase in mitochondrial activity redistributes mitochondria to membrane protrusions of migrating cells, which is necessary to increase cell migration in the presence of adipocyte vesicles. Our results provide key insights into the role of extracellular vesicles in the metabolic cooperation that takes place between adipocytes and tumors with particular relevance to obesity. Synopsis: Extracellular vesicle (EV)‐mediated communication between adipocytes and neighbouring cancer cells is known to promote tumour progression, but the underlying mechanism remains ill‐defined. Adipocyte‐derived extracellular vesicles laden with enzymatic machinery and lipid substrates promote fatty acid oxidation and aggressiveness of melanoma cells, a process that is amplified in obesity. Adipocytes promote melanoma aggressiveness through EV‐mediated delivery of fatty acids and enzymes involved in fatty acid oxidation to cancer cells. Obesity boosts the effect of adipocyte‐derived EVs on melanoma cells, due to the increased loading of fatty acids, but not enzymes, into EVs. Lipophagy and remodelling of mitochondrial network in melanoma cells promote fatty acid oxidation and cancer cell migration, respectively. Abstract : Adipocyte‐derived extracellular vesicles laden with enzymatic machinery and lipid substrates promote fatty acid oxidation and aggressiveness of melanoma cells, a process that is amplified in obesity.